Understanding Oral Oncology and its Changes in Dynamics in Nepal - Shrestha, Aaniya (Europasian Journal of Medical Sciences, 2021)
With the increase in smoking habits, oral cancer is turning into a threat among smokers. It is also due to a lack of awareness among people, oral cancer is increasing rapidly. The increased rate of illiterate people in Nepal has been a reason for a change in dynamics. Due to a lack of awareness, people are diagnosed late with cancer which leads to an increased mortality rate. So, awareness is a must for the reduction of oral cancer. In most cases, surgery is the best chance. Since people in Nepal are mostly from middle-class families, it highly impacts their life. The article primarily addresses the incidence of oral cancer in Nepal. It also emphasizes the risk factors and causes of oral cancer along with its diagnosis and surgery.